A Treatise on the Use of the Tenses in Hebrew and Some Other Syntactical Questions - Driver, S. R. (William b. Eerdmans Publishing Company , Dove Bookseller, 1998)
The original publication of A Treatise on the Use of the Tenses in Hebrew and Some Other Syntactical Questions (1894) launched S. R. Driver's career and placed him at the forefront of Hebrew grammar and biblical studies. The reason is simple: this work was the first attempt in English to expound the principles of Hebrew syntax on lines at once philosophical and scientific. All modern study of Hebrew has been founded on the Tenses, and it remains perhaps the most interesting and original book that Drive wrote. Its final edition was hailed as the best single study of the Hebrew verbal system. Even critics conceded it to be an exciting and brilliant work that shaped future discussion of the Hebrew and Semitic verb.